2016
DOI: 10.1021/acs.jafc.6b03001
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of RA on Myocardial Infarction-Induced Cardiac Fibrosis via AT1R/p38 MAPK Pathway Signaling and Modulation of the ACE2/ACE Ratio

Abstract: Rosmarinic acid (α-o-caffeoyl-3,4-dihydroxyphenyllactic acid, RA) is a major active constituent of Rosmarinus officinalis Linn. (rosemary) having significant anti-inflammatory, anti-apoptotic, and antioxidant effects. However, the cardioprotection of RA is still not understood. The present study was designed, for the first time, to investigate the cardioprotection of RA on myocardial infarction (MI)-induced cardiac fibrosis and to clarify the possible mechanisms. MI was induced in adult rats by left anterior d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
4
35
1
Order By: Relevance
“…Our results demonstrate that the concentration of Ang-(1–7) increases significantly with the administration of foliar extracts, but not with their combination ( Figure 6 a). This finding is in accordance with those published by other authors who used rosmarinic acid and observed an increase in ACE2 expression [ 37 ]. The increase in the concentration of Ang-(1–7) would lessen the concentration of ROS and might protect the heart during the period of ischemia.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results demonstrate that the concentration of Ang-(1–7) increases significantly with the administration of foliar extracts, but not with their combination ( Figure 6 a). This finding is in accordance with those published by other authors who used rosmarinic acid and observed an increase in ACE2 expression [ 37 ]. The increase in the concentration of Ang-(1–7) would lessen the concentration of ROS and might protect the heart during the period of ischemia.…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrate that the infarction significantly increases the concentration of Ang II, while treatments with Ro and Co significantly decreased its concentration ( Figure 4 b). Using adult rats administered with rosmarinic acid, Liu et al [ 37 ] found a decrease in the expression of ACE. Similarly, in our study, Ang II values decreased in Ro -treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Inhibition of the MAPK signalling pathway has been regarded as a potential therapeutic target for ageing‐related fibrosis and other degenerative changes, such as the inhibition of apoptosis singnal regulated kinase 1 (ASK1) (a ROS sensitive kinase belongs to MAKKK family) to alleviate oxidative stress by blocking downstream p38MAPK signalling . Cardiac fibrosis can also be alleviated by other small molecules, including scutellarin, rosmarinic acid and phosphocreatine, through inhibition of MAPK signalling …”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…In vivo , rosemary extract supplementation improved the oxidative stress status in the heart of aged rats[19, 20]. Furthermore, rosmarinic acid reduced myocardial damage blood pressure in hypertensive rats fed a high fructose diet[15] and protected the heart against cardiac dysfunction and fibrosis after MI in rats[21]. However, little is known about the effect of rosemary leaves intake in morphology and ventricular function after myocardial injury.…”
Section: Introductionmentioning
confidence: 99%